Interrelation between Qai’lullah, Blue Light Exposure and Neurocognitive Performances: A Short Review - Fadzil, Nur Farhana; Othman, Siti Amira (Journal of Quranic Sciences and Research, 2021)
Qai’lullah or napping is a phenomenon that is widely practiced in the world. Islam advocates mid-day napping as it is primarily practiced by the Prophet Muhammad (pbuh). Scientists and scholars also acknowledge the benefits beyond this practice after various research and studies done. Hence, this article emphasizes topic of sleep in Islamic insight, their stages of sleeps according to Quran and the practiced of Qai’lullah or mid-day napping. The effect associated with Qai’lullah are also being reviewed including improved the neurocognitive performance, alertness, recover the loss night sleep and enhanced the quality, increased memory consolidation as well as interrelation of light exposure to circadian rhythm of human being.